Parent’s Readiness When Children Face-To-Face Learning During the Covid-19 Pandemic - Sri Rahyanti Ni Made; Anak Agung Istri Wulan Krisnandari (Nursing and Health Sciences Journal (NHSJ), 2023)
The decline in the number of COVID-19 cases impacting on the government decision of back-to-normal life policy. This affects the education sector to switch to offline or face-to-face learning methods with the strict application of health protocols. Parents plays the role to prepare their children to comply with health protocols while attending the offline study. The purpose of the study was to identify parent’s readiness to prepare their children for face-to-face learning during the COVID-19 pandemic. This study is a descriptive study with cross sectional design. The sampling method used was non-probability sampling. The respondents of this study was 68 respondents. The data collection tool used is a questionnaire. The results of this study indicated that 100% of parents have good readiness for children learning face-to-face to school during a pandemic. All parents have readiness for children who will learn face-to-face at school during the covid-19 pandemic